Acute kidney injury in 18 cats after subcutaneous meloxicam and an update on non‐steroidal anti‐inflammatory drug usage in feline patients in Australia. Issue 3 (5th December 2022) - Wun, MK; Leister, E; King, T; Korman, R; Malik, R
Abstract : Objectives: Acute kidney injury (AKI) is a well‐known but poorly documented adverse effect of non‐steroidal anti‐inflammatory drugs (NSAIDs) in cats. We aimed to describe instances of NSAID‐associated AKI in cats and survey Australian veterinarians on NSAID use in acute settings. Methods: Medical records of cats that developed an AKI subsequent to the administration of meloxicam were obtained by searching the databases of seven practices in Queensland, as well as by contemporaneously contacting select veterinary colleagues of the authors in both general and specialist small animal practice. An online questionnaire was created for the survey, and the URL distributed to Australian practitioners. Results: A total of 18 cases were retrieved, all of which received injectable meloxicam. The indication(s) for its use and the dosage prescribed were within the manufacturer's recommendations for Australian veterinarians. The majority of cases (13/18 cats) received the label dose of 0.3 mg/kg subcutaneously (SC) on the day of the procedure. In 12/18 cats, the injection was given in association with general anaesthesia or sedation. Fourteen cats survived to hospital discharge. Of 187 survey respondees, 89% routinely administered NSAIDs for surgery‐related analgesia, with 98% prescribing meloxicam and 84% of these giving it SC. Ninety percent of respondees routinely administered NSAIDs for non‐surgical‐related analgesia, with 99% prescribing meloxicam and 35% of those giving it SC. Conclusions and Relevance: We strongly recommend that practitioners avoid prescribing meloxicam SC in cats. This recommendation is emphatic in situations where concurrent dehydration and/or hypotension are possible.